GEOS-Chem v11-01 for simulating tropospheric aerosols over the western North Atlantic Ocean - Liu, Hongyu; Zhang, Bo (Zenodo, 2024)
This is the GEOS-Chem v11-01 code used in the manuscript: Liu, H., Zhang, B., Moore, R. H., Ziemba, L. D., Ferrare, R. A., Choi1, H., Sorooshian, A. Painemal, D., Wang, H., Shook, M. A., Scarino, A. J., Hair, J. W., Crosbie, E. C., Fenn, M. A., Shingler, T. J., Hostetler, C. A., Chen, G., Kleb, M. M., Luo, G., Yu, F., Tackett, J. L., Vaughan, M. A., Hu, Y., Diskin, G. S., Nowak, J. B., DiGangi, J. P., Choi, Y., Keller, C. A., and Johnson, M. S.: Tropospheric aerosols over the western North Atlantic Ocean during the winter and summer campaigns of ACTIVATE 2020: Life cycle, transport, and distribution, submitted to Atmos. Chem. Phys., April 2024.